A review of recent development: Transport and performance modeling of PEM fuel cells. (1st March 2016) - Wu, Horng-Wen
Highlights: This study reviews 2010–2015 two- and three-dimensional models on PEM fuel cells. Characteristics of transport in membrane, catalyst layers, gas diffusion layers, and channel are studied. This review offers valid findings for improving transport and performance of PEM fuel cells. This review presents a few highlighted areas on PEM fuel cells to be fundamentally realized. Abstract: This study reviews technical papers on transport and performance modeling of proton exchange membrane (PEM) fuel cells during the past few years. The PEM fuel cell is a promising alternative power source for various applications in stationary power plants, portable power device, and vehicles. PEM fuel cells provide low operating temperatures and high-energy efficiency with zero emissions. A PEM fuel cell is a multiple distinct parts device and a series of mass, momentum and energy transport through gas channels, electric current transport through membrane electrode assembly and electrochemical reactions at the triple-phase boundaries. These transport processes play crucial roles to determine electrochemical reactions and cell performance, so studies on the transport and performance modeling have been done deeply. This review shows how these modeling studies offer valid findings for transport and performance modeling of PEM fuel cells and recommendations that can be applied in enhancing transport processes for improving the cell performance.